LEXICALLY NARRATIVE ANALYSIS OF ‘KEEP YOUR FRIENDS CLOSE’ FROM EPIC: THE MUSICAL IN EFL LEARNING - Neviana Ramadhini; Yohanes Gatot Sutapa Yuliana Yuliana (Jurnal Ilmiah Spectral, 2026)
This study aimed to analyze the narrative and lexical aspects of Jorge Rivera-Herran's song "Keep Your Friends Close" from Epic: The Musical and examine the pedagogical value in English as a Foreign Language (EFL) learning. Using a mixed-methods design, the study combines textual analysis with empirical data collected from 31 EFL students through questionnaires and written responses. Despite the majority of participants being unfamiliar with The Odyssey or Epic Literature, findings reveal moderate vocabulary recognition (mean score 160/200, median 170) and strong narrative comprehension (86% identifying loyalty/betrayal as the main theme), even among those unfamiliar with The Odyssey, indicating that narrative-driven songs enhance contextual vocabulary uptake and cultural understanding. These results affirm musical texts as effective EFL tools for bridging literal and inferential meaning.